2012
DOI: 10.1002/hbm.21475
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of ICA‐derived EEG functional connectivity in the resting state

Abstract: An emerging issue in neuroscience is how to identify baseline state(s) and accompanying networks termed "resting state networks" (RSNs). Although independent component analysis (ICA) in fMRI studies has elucidated synchronous spatiotemporal patterns during cognitive tasks, less is known about the changes in EEG functional connectivity between eyes closed (EC) and eyes open (EO) states, two traditionally used baseline indices. Here we investigated healthy subjects (n = 27) in EC and EO employing a four-step ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
108
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(126 citation statements)
references
References 133 publications
(129 reference statements)
17
108
1
Order By: Relevance
“…Checking the literature further, we can confirm that the 13 ROIs suggested in Chen et al [39] are in line with previous fMRI literature investigating the resting-state network during EO and EC conditions [40,41,42]. Furthermore, the interhemispheric asymmetry present in Chen et al [39] is also present in other articles studying the resting-state networks during EO and EC [40]. …”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…Checking the literature further, we can confirm that the 13 ROIs suggested in Chen et al [39] are in line with previous fMRI literature investigating the resting-state network during EO and EC conditions [40,41,42]. Furthermore, the interhemispheric asymmetry present in Chen et al [39] is also present in other articles studying the resting-state networks during EO and EC [40]. …”
Section: Methodssupporting
confidence: 89%
“…Regions of Interest (ROIs) were chosen according to Chen et al [39] who identified 13 brain regions that show increased connectivity in the alpha band in an EO state with respect to an EC resting-state. Checking the literature further, we can confirm that the 13 ROIs suggested in Chen et al [39] are in line with previous fMRI literature investigating the resting-state network during EO and EC conditions [40,41,42].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found six components related to the ERP and show how the neuronal sources found using gICA can also be found applying ICA to each subject. A study of the "resting state networks", obtained by EEG during eyes closed and eyes open, was done by Chen et al [32], finding connectivity patterns between thirteen neuronal sources comparable with those found by fMRI. The analysis was based in gICA, to extract the neuronal sources related to resting state, and inverse solution methods to locate the neuronal sources in the brain cortex.…”
Section: Introductionmentioning
confidence: 94%
“…An early electrophysiological study (Martindale 1977) reported no consistent relationship between creativity and resting-state EEG alpha power, an EEG measure which was shown by several studies to be positively related to DMN activity (Chen et al 2008(Chen et al , 2013Laufs et al 2003;Mantini et al 2007). Yet, in a later study, resting-state EEG alpha power was only weakly positively correlated with divergent thinking scores, while coherence measures in all frequency bands-including alpha-negatively correlated with divergent thinking scores (Jaušovec and Jaušovec 2000).…”
Section: Implications For the Disinhibitory Notion Of Divergent Thinkingmentioning
confidence: 99%